Three dimensional anthropometric measurements of the distal femur and proximal tibia for the Malay population - Hussain, Fitdriyah; Abdul Kadir, Mohammed Rafiq; Zulkifly, Ahmad Hafiz; Sa'at@Yusof, Azlin; Abd. Aziz, Azian (2010)

(untitled)
Current available implant for total knee arthroplasty normally based on the western population knee. Asian knee were different from the European knee. A prospective morphometric study of the knee joint was carried out. One hundred (100) participants consisting of 50 males and 50 females were scanned using computed tomography equipment. The age of the participants vary from 19 to 38 years old, with height variation from 141cm to 182cm, and weight from 39kg to 110kg. The knee joints were reconstructed in three dimensions from the CT datasets and measurements were done using computational method. The anterior-posterior (AP) length and the medial-lateral (ML) width of the distal femur and proximal tibia were measured. For the distal femur, the average dimension for the anterior-posterior (fAP) is 60.7±4.7mm and for the medial-lateral (fML) is 69.7±6.1mm. For proximal tibia, the average dimension for the anterior-posterior (tAP) is 48.1±4.7mm and for the medial-lateral (tML) is 72.6±6.8mm. These data provide the basis for the development of femoral components for high flexion total or partial knee replacement for Malaysian population.